2005
DOI: 10.1590/s0100-204x2005001100008
|View full text |Cite
|
Sign up to set email alerts
|

Relação entre distribuição de nitrogênio e colonização por bactérias diazotróficas em cana-de-açúcar

Abstract: Resumo -O objetivo deste trabalho foi avaliar a relação entre a distribuição de nitrogênio na planta e a colonização por Gluconacetobacter diazotrophicus e Herbaspirillum spp. Foi implantado um experimento em parcelas subdivididas, tendo como tratamentos quatro genótipos: SP70-1143, SP79-2312 (híbridos) Relationship between nitrogen distribution and diazotrophic bacteria colonization in sugarcaneAbstract -The objective of this work was to evaluate the relation between nitrogen distribution in plants of sugarc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…In our study, the high number of isolates found in the stalks and leaves of sugarcane indicates that these parts of the plant can host a high bacterium diversity as also reported by Gomes et al (2005) and Suman et al (2005), which confirmed that the stalk and leaves of sugarcane present high occurrence of PGPBs. This finding is important for sugarcane because its propagation occurs through a vegetative way and, thus, other plants can disseminate these PGPBs strongly.…”
Section: Resultssupporting
confidence: 87%
“…In our study, the high number of isolates found in the stalks and leaves of sugarcane indicates that these parts of the plant can host a high bacterium diversity as also reported by Gomes et al (2005) and Suman et al (2005), which confirmed that the stalk and leaves of sugarcane present high occurrence of PGPBs. This finding is important for sugarcane because its propagation occurs through a vegetative way and, thus, other plants can disseminate these PGPBs strongly.…”
Section: Resultssupporting
confidence: 87%
“…Herbaspirillum seropedicae (BALDANI et al, 1986) and Azospirillum brasilense (TARRAND et al, 1978) can colonize roots of cereals, and their efficiency to transfer fixed nitrogen to plants was already described in rice and sugarcane (BALDANI et al, 1997, BALDANI;BALDANI, 2005, BHATTACHARJEE et al, 2008GUNRI, 2015). H. seropedicae in wheat crops can substitute nitrogen fertilization, according to a greenhouse experiment (NEIVERTH et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The beneficial effects of PGPB on plants depends on many factors, such as soil type, plant age, physiological stage and genotype, and the bacterial strain specificity (BALDANI; BALDANI, 2005, ROESCH et al, 2006. However, wheat genotypes have different capacities of association with bacteria.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many techniques have been applied with success to monitor the presence (Oliveira et al, 2009;Silva-Froufe et al, 2009) or even quantify (Gomes et al, 2005;Munoz-Rojas and Caballero-Mellado, 2003) the inoculated bacterial strains within plants.…”
Section: Introductionmentioning
confidence: 99%